Reducing Wait Time for Lung Cancer Diagnosis and Treatment: Impact of a Multidisciplinary, Centralized Referral Program. Issue 3 (August 2018) - Common, Jessica L.; Mariathas, Hensley H.; Parsons, Kaylah; Greenland, Jonathan D.; Harris, Scott; Bhatia, Rick; Byrne, Suzanne C.
Background: A multidisciplinary, centralized referral program was established at our institution in 2014 to reduce delays in lung cancer diagnosis and treatment following diagnostic imaging observed with the traditional, primary care provider–led referral process. The main objectives of this retrospective cohort study were to determine if referral to a Thoracic Triage Panel (TTP): 1) expedites lung cancer diagnosis and treatment initiation; and 2) leads to more appropriate specialist consultation. Methods: Patients with a diagnosis of lung cancer and initial diagnostic imaging between March 1, 2015, and February 29, 2016, at a Memorial University–affiliated tertiary care centre in St John's, Newfoundland, were identified and grouped according to whether they were referred to the TTP or managed through a traditional referral process. Wait times (in days) from first abnormal imaging to biopsy and treatment initiation were recorded. Statistical analysis was performed using the Wilcoxon rank-sum test. Results: A total of 133 patients who met inclusion criteria were identified. Seventy-nine patients were referred to the TTP and 54 were managed by traditional means. There was a statistically significant reduction in median wait times for patients referred to the TTP. Wait time from first abnormal imaging to biopsy decreased from 61.5 to 36.0 days ( P < .0001). Wait time from first abnormal imaging to treatment initiation decreased from 118.0 to 80.0 days ( P < .001). The percentage of specialist consultations that led to treatment was also greater for patients referred to the TTP. Conclusions: A collaborative, centralized intake and referral program helps to reduce wait time for diagnosis and treatment of lung cancer.